The Parturients with Anti-HIV Positive in Taksin Hospital - Chintanadilok, Adisak (Journal of Health Science of Thailand, 1995)
From January 1992 to December 1994, patients with anti-HIV positive delivered at Taksin Hospital were collected. From the analysis showed the prevalence rate increase year by year from 0.9% in the first year to 1.4% in 1994. Group of unregistered patients trended to have higher prevalence of anti-HIV positive than the registered group. Most of anti-HIV positive patients were low parity and young age. Major route of delivery in this group was normal vaginal delive of tubal resection after delivery was low, in spite of pre-test and post-test counselling services. The co-operation of male partners for screening of anti-HIV was poor. The method of management for these patients was discussed according to the facility of Taksin Hospital.